DIGITAL TECHNOLOGIES FOR COGNITIVE LINGUISTICS STUDIES IN MAGISTRACY - Petrova, Inna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The field of higher education in Russia is undergoing significant changes that require reviewing past practices and professional activities. This article aims to study the potential of using modern digital technologies in linguistic experiments in cognitive linguistics regarding writing master’s degree theses.The analysis of recent cognitive studies has shown that the area for this research is diverse and includes investigating aspects of cognitive semantics, translation techniques, concordance, phrase variability, and others. Research results show that cognitive science widely uses empirical data received through digital technologies such as Google. This digital tool can be accessible and suitable for linguistic experiments and the author demonstrates its application.The paper presents a model of the linguistic experiment on studying the variability of the structure of a conceptual binominal phrase in Russian and English. According to the obtained results, Russian users of the Internet feature a higher tendency for changing the order the binomial concepts than the English-speaking ones. These data provide language material for conclusions and further considerations from a cognitive perspective. The framework of this experiment can be a motivating factor for those who want to master their research and language skills in the magistracy.